THE ROLE OF DIGITAL TOOLS FOR LEARNING ENGLISH - Vakhobova Mukhlisa Khuvaydilla kizi,; Bakhtiyorova Maftuna Bakhtiyorovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Digital tools have become essential in English language education, enhancing learning beyond traditional teacher-centered methods. Technologies such as online  exercises,  apps,  video  calls,  and  multimedia  resources  support  all  language skills, promote autonomous learning, and make lessons more interactive and engaging. Theories  like  constructivism,  Communicative  Language  Teaching,  and  Multimedia Learning  Theory  explain  how  digital  tools  improve  comprehension,  retention,  and practical language use. Scholars including Chapelle & Sauro, Levy, and Stockwell emphasize that, when used with clear pedagogical goals, technology can significantly enhance English learning.